Indications of Unfair Business Competition in Tiktok's Acquisition of Tokopedia Shares - Pryanka Humaira Febriandhara; Sinar Aju Wulandari (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
The development of digital technology has driven significant transformation in the business world, including the emergence of e-commerce as a new form of trade activity. One of the cases that has arisen as a result of this development is the acquisition of Tokopedia shares by TikTok. This acquisition is considered to indicate potential unfair business competition. This research aims to analyze whether the acquisition of Tokopedia shares by TikTok shows signs of unfair business competition and whether there have been legal measures taken by the Indonesian Competition Commission (KPPU) in response. The research employs a statute approach, a case study, and a conceptual approach. The results of the study indicate that there are signs of unfair business competition in the acquisition of Tokopedia by TikTok. KPPU has also carried out its supervisory function by conducting an assessment and issuing a conditional approval as part of its efforts to maintain fair business competition.